2016
DOI: 10.3109/02699206.2015.1120346
|View full text |Cite
|
Sign up to set email alerts
|

How early L2 children perform on Italian clinical markers of SLI: A study of clitic production and nonword repetition

Abstract: Early second language (EL2) learners generally perform more poorly than monolinguals in specific language domains, presenting similarities with children affected by specific language impairment (SLI). As a consequence, it can be difficult to correctly diagnose this disorder in EL2 children. The current study investigated the performance of 120 EL2 and 40 age-matched monolingual children in object clitic production and nonword repetition, which are two sensitive clinical markers of SLI in Italian. Results show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
78
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(87 citation statements)
references
References 44 publications
6
78
2
1
Order By: Relevance
“…Note that such finding is in line with previous research based on early L2 Italian pre-school children, which showed a performance on non-word repetition comparable to their monolingual peers. By contrast, their ability in other tasks of morpho-syntactic knowledge appeared significantly lower with respect to monolinguals, though not directly comparable to that of SLI children (Vender et al, 2016).…”
Section: Discussioncontrasting
confidence: 60%
“…Note that such finding is in line with previous research based on early L2 Italian pre-school children, which showed a performance on non-word repetition comparable to their monolingual peers. By contrast, their ability in other tasks of morpho-syntactic knowledge appeared significantly lower with respect to monolinguals, though not directly comparable to that of SLI children (Vender et al, 2016).…”
Section: Discussioncontrasting
confidence: 60%
“…In this sense, the results put forward by Vender et al (2016) suggest that monolingual and EL2 children's profiles in clitic production differ in quantitative and qualitative terms. Although EL2 children underperformed the monolinguals, producing a lower number of clitics, they did not omit the pronoun (which constitutes the typical behavior of SLI children), but produced an incorrect (wrongly inflected) clitic instead.…”
Section: The Acquisition Of Clitics In Early L2 and Bilingual Childrenmentioning
confidence: 93%
“…More recently, (Vender et al 2016) administered a clitic elicitation task to 120 preschool EL2 children that were exposed to Italian as their L2 (3.5 years in average) and were speaking Albanian, Arabic, or Romanian as their first language, and compared their performance to that of 40 monolingual Italian children. The authors aimed not only to compare monolingual and EL2 children in clitic production, but also to evaluate the role of exposure to Italian, as well as competence in the L2, as predictors of the performance in the task.…”
Section: The Acquisition Of Clitics In Early L2 and Bilingual Childrenmentioning
confidence: 99%
See 2 more Smart Citations